Perbandingan Spinal Brace Fleksibel dan Rigid pada Skoliosis Idiopatik Remaja: A Systematic Review and Meta Analisis - Raden Achmad Candra Putra; Satria Ardianuari; Somsak Kuptniratsaikul (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This systematic review and meta-analysis aimed to assess the clinical outcomes of flexible versus rigid spinal braces in managing curve progression among adolescents with idiopathic scoliosis (AIS). A comprehensive search was conducted in PubMed, Embase, and Scopus up to July 7, 2021. Eligible studies directly compared the effectiveness of both brace types in AIS patients. Two independent reviewers performed screening, quality assessment using the Newcastle-Ottawa Scale and Cochrane risk of bias tool, and data extraction. From 39 full-text articles, 2 randomized controlled trials and 4 cohort studies met the inclusion criteria. Meta-analyses were performed using the Mantel-Haenszel method with a random-effects model. Pooled results showed a significant difference in treatment success at skeletal maturity between flexible and rigid braces [RR 0.72; 95% CI (0.58–0.88); P=0.001]. Subgroup analyses confirmed the robustness of these findings (P=0.001; I²=0%). Conversely, no significant differences were found in curve progression beyond 45° or curve stability two years after skeletal maturity. Overall, rigid braces made from thermoplastic materials demonstrated superior effectiveness in preventing curve progression until skeletal maturity in adolescents with idiopathic scoliosis. These results reaffirm the clinical importance of rigid bracing as the current standard of care in AIS management.